Pendampingan Berbasis Participatory Action Research pada UMKM Warung Sambal Cidero Kediri: Penguatan Sertifikasi Halal dan Strategi Price value untuk Meningkatkan Daya Saing Usaha - Afni Tri Rahayu; Pendik Dwi Prasetyo; Ratna Della Ashari; Sudarmiatin Sudarmiatin; Ruly Wiliandri (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
Micro, Small, and Medium Enterprises in the culinary sector face multiple competitive pressures encompassing product legality, consumer trust, and the effectiveness of value communication. This Community Service activity was conducted at Warung Sambal Cidero, a culinary MSME in Kediri City, from March 28, 2026, to April 25, 2026, using a Participatory Action Research approach with four cycles: planning, action, observation, and reflection. Two main interventions were implemented: strengthening halal certification through supply chain audits, developing a Halal Product Assurance System, and assisting with SIHALAL-BPJPH registration; and improving price value strategies through consumer perception-based rebranding, value-based pricing, and optimizing digital marketing. The reflective evaluation confirmed substantive changes in the business owner's understanding of halal as a strategic business instrument, improvements to the raw material recording system, and a shift in consumer perception from a price-oriented to a value-oriented one. This activity contributes to the theoretical integration of the PAR approach and strategic management and marketing frameworks in the context of Indonesian culinary MSMEs.